Ageism at Work: Students' Perspective - Barbara Grah; Sandra Penger (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
Ageism symbolises negative beliefs, opinions, expectations, attitudes, and stereotypes about age. Ageism is frequently recognised as a crucial barrier to obtaining and retaining work. In dealing with older people in the workplace, a study showed that regardless of the perceived challenges (e.g., the ageing workforce), most employers take no necessary measures or actions to retain and recruit older workers or advance their productivity (Van Dalen et al., 2009). Younger generations must become aware of this phenomenon and act proactively towards intergenerational support. Therefore, we performed the study based on the content analysis of the first-year students of the School of Economics and Business perspective on the ageism phenomenon. Specifically, we investigated the topic under study through qualitative research. Namely, we collected their opinions and presented their results with explanatory quotations that offer a phenomenological alternative to the social perspective of ageism in the workplace, advancing research in an organisational context through students' perspectives. Practically, our study contributes to the understanding of the lifelong challenges that our societies face and a possible pathway to addressing the broader future perspective by linking different generations.
Keywords: J26; J28; J60; 330; ageism; content analysis; students' perspective